Correction: Sterol Biosynthesis and Azole Tolerance Is Governed by the Opposing Actions of SrbA and the CCAAT Binding Complex. - Fabio Gsaller; Peter Hortschansky; Takanori Furukawa; Paul D Carr; Bharat Rash; Javier Capilla; Christoph Müller; Franz Bracher; Paul Bowyer; Hubertus Haas; Axel A Brakhage; Michael J Bromley (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1005775.].